Pengembangan Perangkat Pembelajaran Berbasis Contoh Lokal untuk Meninggkatkan Kemampuan Berpikir Kritis pada Konsep Fisika - Lumalaga, Nurfajrin; Yuliyanti (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2024)
This research aimed to describe the quality of the learning tool which had 3 aspects, and those were validity, practical, and effective based on local wisdom in Lolontup game by using guided,inquiry learning model on the GLBB and parabolic motion which was done in two meetings at SMAN 1 Masama. This research applied development research method with the development model of ADDIE. The data analysis techniques used was the analysis of data validaiion, analysis of interview result from teachers and students, and analysis of data vali'dity on the competency assessment instruments. The analysis result revealed that the overall learning device fulfilled the criteria of valid, practical, and effective. The validity aspect revealed that based on the result'of expert validition, it showed that the learning device was valid and could be used with a little revision.